Efficacy and Safety of Doxazosin in Medical Expulsive Therapy for Distal Ureteral Stones: A Systematic Review and Meta-analysis - Ma, Li; Zou, Shiyue; Yang, Lu; Wang, Fan (Urology Journal, 2020)
Purpose: Alpha-blockers have been proven as an effective method for increasing the stone expulsion rate of distal ureteral stones. Limited studies have focused on doxazosin; its efficacy remained unclear. We performed this meta-analysis to investigate the efficacy and safety of doxazosin for patients diagnosed with distal ureteral stones less than 10mm. Materials and Methods: We systematically searched Ovid MEDLINE®, Cochrane Library, EMBASE, and PubMed for articles comparing doxazosin and conventional care or tamsulosin for distal ureteral stones through October 2019. The outcome measures were stone expulsive rate (SER), stone expulsive time (SET), pain episodes, analgesics consumption, and adverse events. Results: We included 12 studies involving 836 participants with distal ureteral stones less than 10mm in our review. The present meta-analysis showed doxazosin could significantly increase SER [RR=1.64,95%CI (1.32, 2.04), P < 0.00001], shorten SET [WMD=-3.97,95% CI (-5.68, -2.27), P < 0.00001] compared with conventional care. In the subgroup analyses, doxazosin showed no benefit in the children subgroup (<16 years old) [RR=1.63,95% CI (0.73,3.64), P =0.23]. No statistically significant difference was observed regarding the effectiveness of doxazosin and tamsulosin in SER, SET, and safety. 9 in 286 participants reported doxazosin-related adverse events; most were mild to moderate. Conclusion: This meta-analysis may suggest that doxazosin is a safe and effective MET for distal ureteral stones less than 10mm. It is not demonstrated to have any significant difference with tamsulosin in SER, SET, and safety. However, it showed no benefits for patients<16 years old.